Efficacy of Kushtadi Choorna Pratisarana in the Management of Sheetada - A Case Study - Vishnu , V V; Naveen, B S; Geetha , Kumari B; Viswam, Ajoy; Namboothiri, Krishnan (International Research Journal of Ayurveda & Yoga, 2022)
Sheetada is explained elaborately in Ayurveda as a type of Dantamoolagataroga (periodontal diseases) In Ayurvedic classics several treatment modalities such as Pratisarana, Gandoosha and Kavala have been mentioned for the management of Sheetada. Kushtadi choorna Yoga is one such formulation which is documented in Ayurvedic literature for treating oral cavity disorders like Raktasrava (bleeding), Kandu (itching) and Ruja (pain). Its anti-inflammatory, antioxidative and antimicrobial factors helps to maintain the strength of gingiva. Gingivitis is an inflammatory response of the gingiva without destruction of the supporting tissues. Inflamed gingiva is clinically recognized by the signs of inflammation such as redness of the gingiva, swelling, bleeding and exudation. In the present study, a 26 year old male having the features of Sheetada was treated with Kushtadi choorna Pratisarana. Marked improvement in the signs and symptoms were observed after treatment.